2011
DOI: 10.1136/gutjnl-2011-301181
|View full text |Cite
|
Sign up to set email alerts
|

Regional colon transit in patients with dys-synergic defaecation or slow transit in patients with constipation

Abstract: Objective-To differentiate dys-synergic defaecation (DD) from normal function and slow transit constipation (STC).Methods-The medical records of 1411 patients evaluated by a single gastroenterologist over a 16-year period at a tertiary medical centre were reviewed. DD was characterised by anorectal manometry and balloon expulsion test. There were 390 patients with DD, and 61 with STC without DD. Transit data from 211 healthy individuals served as controls. The primary endpoints were overall colonic transit (ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 46 publications
3
98
1
2
Order By: Relevance
“…Our previous study showed that overall colonic transit was delayed in patients with dyssynergic def- ecation and in those with slow transit constipation in the absence of evacuation disorders, relative to healthy volunteers. 6 We previously showed the higher proportion of isotope in the left colon at 48 hours in patients with dyssynergic defecation compared to those with only slow transit constipation. However, in that study, patients with either normal or slow colonic transit were included in the group of dyssynergic defecation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study showed that overall colonic transit was delayed in patients with dyssynergic def- ecation and in those with slow transit constipation in the absence of evacuation disorders, relative to healthy volunteers. 6 We previously showed the higher proportion of isotope in the left colon at 48 hours in patients with dyssynergic defecation compared to those with only slow transit constipation. However, in that study, patients with either normal or slow colonic transit were included in the group of dyssynergic defecation.…”
Section: Discussionmentioning
confidence: 99%
“…We performed anorectal manometry and balloon expulsion tests as previously described; theses included traditional and high resolution manometry, 6 and the maximum resting and squeeze anal pressures were expressed as mmHg. After the manometry study, a latex balloon was inserted into the rectum and filled with 50 mL water.…”
Section: Anorectal Manometry and Balloon Expulsion Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…CIC is associated with reduced colonic motility; however, in one tertiary referral study, almost 30% of patients with chronic constipation had evidence of rectal evacuation disorders (67). Patients with evacuation disorders are less likely to respond to colonic prokinetic agents, as demonstrated in a comparison of prucalopride and PEG3350 in patients with chronic constipation, many of whom endorsed symptoms suggestive of rectal evacuation disorders (68).…”
Section: Cic and Oicmentioning
confidence: 99%